Towards a Maturity Model for Data on the Web Initiatives - Muniz, Rayelle Vera Cruz Silva; Silva, Karina Moura; Oliveira, Marcelo de Sousa; Lóscio, Bernadette Farias (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2020: Anais do XVI Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2020.13788, 2020)
Data on theWeb publishing and consumption practices have increased as theWeb has become more than just a means of entertainment. In addition, many processes, guidelines and best practices have been proposed to facilitate both publication and data consumption. However, many data providers are unaware or does not make use of these initiatives, been unable to meet the challenges that arise when publishing data on the Web, which increasingly generates content-poor datasets, even with a domain of relevance. Given this scenario, this paper proposes a Data on the Web Maturity Model to assess the maturity of organizations or individuals in the process of publishing data on the Web from a technical point of view. The model was evaluated through a focus group, where it was possible to collect qualitative data in order to evolve the word. From the collected feedback, we arrived at version 1.0 of the model, presented in this article. Although a large part of the suggestions were included, some were registered for later consideration in a new evaluation.